Self-Determination in English Learning among Visually Impaired Students: The Role of an AI-Based Braille Audio Dictionary - Ratih Zatil Imandari; Urai Salam; Venny Karolina; Ahmad Yani T.; Eka Ariyati; Nor Fazlin Mohd Ramli (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to analyze the self-determination of visually impaired students in learning English through the use of a Braille dictionary equipped with Artificial Intelligence (AI)-based audio, viewed from the perspective of Self-Determination Theory (SDT), which includes autonomy, competence, and relatedness. The research employed a qualitative approach with a case study design. Data were collected through interviews with visually impaired students, teachers, and parents and analyzed using thematic analysis through coding procedures. The findings indicate that the competence dimension appeared most dominantly, followed by autonomy, which reflects increased learner independence through the use of assistive technology. The improvement in competence was mainly influenced by the natural and clear AI-generated pronunciation, which enabled students to repeatedly listen to, imitate, and self-correct English pronunciation independently. In addition, the ease of accessing audio through the integrated Braille dictionary supported students’ confidence and learning autonomy. Meanwhile, relatedness emerged through interactions with teachers and parents, although it was relatively limited. These findings suggest that the Braille dictionary with AI-based audio has the potential to enhance accessibility, learner independence, and English learning abilities among visually impaired students, thereby supporting more inclusive learning practices.